The Synthesis of π,n-Complexes of 1-Thio-1,3-dienes with Chromium Group Metals. The Inner-Sphere Hydrophosphorylation of α-Enethiones - Kuramshin A.I.; Kolpakova E.V.; Kuramshina E.A.; Cherkasov R.A.; Galkin V.I. (Учёные записки Казанского университета: Серия Естественные науки)
New 1-thio-1,3-diene complexes of chromium(0), molybdenum(0), and tungsten(0) with the biden-tate bonding of unsaturated ligand to the metal’s core via the π-system of the C=C bond and sulfur lone electron pair of heterodiene are obtained. Quantum-chemical calculations reveal geometry, electron structure, and formation free energies of these complexes, as well as factors governing the coordination mode. Hydrophosphorylation of the complexes begins from the attack of H-dialkylphosphonate towards the thiocarbonyl group; the generated organometallic α-mercaptophosphonates subsequently undergo the mercaptophosphonate-thiolphospate and thiolphosphate-thionphosphate rearrangements with organ-ophosphorus compounds remaining bound to the metal’s core.